Westonci.ca provides a collaborative platform for sharing and gaining knowledge. Join our interactive Q&A community and get reliable, detailed answers from experienced professionals across a variety of topics.

## Sagot :

1. Sustituyamos [tex]\( x \)[/tex] por 1 en la ecuación:

[tex]\[ y = 5(1)^4 + 3(1) \][/tex]

2. Calculamos el valor de [tex]\( (1)^4 \)[/tex]:

[tex]\[ (1)^4 = 1 \][/tex]

3. Multiplicamos este resultado por 5:

[tex]\[ 5 \times 1 = 5 \][/tex]

4. Luego, multiplicamos [tex]\( 3 \)[/tex] por [tex]\( 1 \)[/tex]:

[tex]\[ 3 \times 1 = 3 \][/tex]

5. Sumamos estos dos resultados:

[tex]\[ 5 + 3 = 8 \][/tex]

Por lo tanto, el valor de [tex]\( y \)[/tex] cuando [tex]\( x = 1 \)[/tex] es:

[tex]\[ \boxed{8} \][/tex]